2021
DOI: 10.1021/acs.jafc.1c02205
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism on the Allergenicity Changes of α-Lactalbumin Treated by Sonication-Assisted Glycation during In Vitro Gastroduodenal Digestion

Abstract: Physical-assisted chemical modification is effective to reduce the allergenicity of α-lactalbumin (ALA). However, there are few in-depth studies on the allergenicity changes of physical-assisted chemical-modified ALA during digestion. The effect of gastroduodenal digestion on the allergenicity changes of ALA treated by sonication-assisted glycation was assessed. Digestion of both ALA and its glycated forms generated peptide fractions, and intact undigested glycated ALA in the hydrolysates still covalently boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…A recent study showed that sonication combined with glycation only caused a small decrease in OVA digestibility under simulated gastric and small intestine conditions but that OVA‐specific IgG and IgE levels were exceedingly low after digestion (W. Yang et al., 2021). Similar phenomena were found in sonication‐assisted glycated α‐lactalbumin (X. Wang, Tu, Ye, et al., 2021), which can be attributed to the shielding effect of the linear epitopes caused by the greater degree of glycation. The allergenicity of β‐lactoglobulin was also significantly reduced by ultrasound combined with glycation modification and subsequent digestion.…”
Section: Food Processing Influences Digestion and Allergenicity Of Fo...supporting
confidence: 72%
“…A recent study showed that sonication combined with glycation only caused a small decrease in OVA digestibility under simulated gastric and small intestine conditions but that OVA‐specific IgG and IgE levels were exceedingly low after digestion (W. Yang et al., 2021). Similar phenomena were found in sonication‐assisted glycated α‐lactalbumin (X. Wang, Tu, Ye, et al., 2021), which can be attributed to the shielding effect of the linear epitopes caused by the greater degree of glycation. The allergenicity of β‐lactoglobulin was also significantly reduced by ultrasound combined with glycation modification and subsequent digestion.…”
Section: Food Processing Influences Digestion and Allergenicity Of Fo...supporting
confidence: 72%
“…As the leading pediatric food allergy, the peanut (Arachis hypogaea L.) allergy (PA) can cause anaphylaxis, and its prevalence has increased dramatically. , Although it is lifelong in most instances, disease-modifying treatments for the PA are lacking . Many attempts have been made to reduce the potential allergenicity of peanut allergens. Previous studies have shown that the allergenicity can be changed by altering the structure and other physicochemical properties of food allergens. …”
Section: Introductionmentioning
confidence: 99%
“…SS treatment, particularly at high temperatures and long processing times, could induce the OVM aggregation, increase surface hydrophobicity, modify the functional groups and amino acids in OVM. These phenomena disrupted and buried some allergen epitopes and made it difficult for the combination of antibodies and antigens [ 14 , 15 ]. Therefore, the allergenicity of OVM was decreased and the anaphylactic reaction in the KU812 cell was inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…The IgG and IgE-binding abilities of the OVM samples were estimated with indirect competitive ELISA according to our previous report [ 14 ]. Rabbit anti-OVM IgG serum and human anti-OVM IgE serum were used to determine IgG-binding ability and IgE-binding ability, respectively.…”
Section: Methodsmentioning
confidence: 99%